El procedimiento de ínfima cuantía determinado en el reglamento general de la ley orgánica del sistema nacional de contratación pública, genera un problema jurídico legal para su aplicación al no permitir que se establezca un proceso único practicable en todas las instituciones del estado sujetas al ámbito de esta ley. - Castillo Delgado, Carlos Byron (2015)
Public procurement in our country reborn as such from the enactment of the new Organic Law of the National System of Public Procurement and Regulation , in all proceedings in that provision is the smallest amount of a process that no major guidelines and guidelines for implementation and execution but nevertheless is one of the most used for the acquisition of goods and services and even for the procurement of works but only for those with only one object and repair, spare , remodeling, adaptation, maintenance or improvement of a building or infrastructure whose reference budget is less than0.0000002 coefficient multiplying the initial statebudget for the financial period. The most I can used to express several discretionary aspects that the law allows, among which we can express: Hiring provider directly performed also the provider does not need to be enabled on the RUC, and the legalization of the handover is executed with the presentation of the bill, a situation that is of concern because the LOSNCP within its legislation establishes the fundamental principles on which public procurement as the legality , transparency, equality and others governed . Then with the process set out in RGLOSNCP, violates these principles and to the competent administrative authority has absolute discretion to omit addressing these requirements and procedures, so it is necessary and urgent to establish a unique and feasible procedure in RGLOSNCP, in order that the fundamental principles of public procurement are respected and step closes the opportunists and corruption that is entrenched in the public service. This work involves analysis of the mechanisms for entities to make possible this type of procedure and carry out the various recruitment processes these without being outside the law, are exempt from certain formalities and requirements. In addition, this work is focused on determining the importance of the principles of legality, transparency and equality; since this procedure can not be executed without a single practicable process, so you have to find the best means to be used for that an effective internal and external control.